Ecotoxicity and Preliminary Risk Assessment of Nonivamide as a Promising Marine Antifoulant - Sujing Liu; Jun Zhou; Xuanxuan Ma; Ying Liu; Xing Ma; Chuanhai Xia (Journal of Chemistry)
The unclear environmental performance of nonivamide limits its application as a marine antifoulant. In this study, the natural degradation of nonivamide was studied in seawater and tap water. The half-life was 5.8 d, 8.8 d, 12.2 d, and 14.7 d in seawater and tap water in photolysis and biolysis, respectively. Furthermore, the ecotoxicity of nonivamide was assessed using marine microalgae, Chlorella vulgaris and Platymonas sp.; EC50,  6 d values on the growth of Chlorella vulgaris and Platymonas sp. were 16.9 mg L−1 and 19.21 mg L−1, respectively. The toxicity and environmental risk of nonivamide on microalgae were significantly decreased due to the natural degradation in seawater.